Desafíos y restricciones de la gestión ambiental orientada a la salud pública en gobiernos locales - Fernández Vásquez, Wiliam (2025)
Public health-oriented environmental management in local governments faces critical challenges due to institutional, financial and technical constraints, together with inadequate waste management and a deficit in reliable data for decision making. This study, through a systematic review based on the PRISMA protocol, analyzes 32 scientific publications selected from international databases such as Scopus and Web of Science, with the aim of identifying constraints and proposing innovative strategies. Key issues include persistent environmental pollution, uncontrolled urban growth and limited citizen participation in environmental initiatives. Despite these challenges, promising strategies emerge such as the adoption of emerging technologies, circular economy approaches and data-driven methodologies for environmental monitoring. In addition, the importance of community education and participation to leverage effective policies is underscored. This analysis highlights the need for a comprehensive approach that strengthens local capacities and fosters multi-sectoral collaboration to achieve sustainable development and a significant improvement in quality of life.